HUBUNGAN PENGETAHUAN PASIEN TIRAH BARING YANG TERLALU LAMA DENGAN KEJADIN DEKUBITUS DI RUMAH SAKIT BANGKATAN PTPN 2 BINJAI TAHUN 2017 - Wirda Faswita (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Humans live most of their lives in bed. In general, staying in bed does not cause problems, it will cause problems if humans do not have enough rest (night rest). During sleep, humans rebuild their energy. Problems will arise if someone who is suffering from an illness takes too long to rest in bed (Stevens, 2010). Based on the experience of researchers during the practice at the Djoelham Binjai General Hospital, there are still patients with bed rest who experience pressure sores, especially in patients who have been lying too long. This is due to the high burden of nurses, while bed rest patients have a very high dependence on nurses due to a lack of knowledge of patients about the procedure of changing positions while lying in bed, from 55 patients who had bed rest long enough to find 30 of them had pressure sores. The type of research used is descriptive with a survey method which aims to find out